السياحة العلاجية الاستشفائية في الجزائر: ولاية ورقلة أنموذجا: دراسة حالة الينابيع الحموية - حسيني، زهور; لخضر، مداح (جامعة قاصدي مرباح - ورقلة, 2022)
تعتبر ولاية ورقلة الأولى وطنيا في عدد المنابع الحموية حيث تزخر بـ39 منبع حموي منها 15 منبعا ذو تدفق وقيمة علاجية عالية من إجمالي 282 منبع على مستوى الجزائر، هدفت الدراسة إلى تبيان واقع هاته السياحة والوقوف على أسباب وإشكاليات تعثرها على مستوى الولاية، بناءا على منهجية استندت إلى، تحليل وصفي لإحصائيات متحصل عليها من الوزارة المعنية بالسياحة والمديرية الولائية للسياحة وثائق وفيديوهات ومقابلات تخص ذات الموضوع مع جهات ذات صلة، وخلصت الدراسة إلى أن إشكالية السياحة العلاجية في شقها الاستشفائي حالة ينابيع المياه الحموية استنادا لمؤشرات التركيز لأصحاب المصلحة بذات المجال ركزت على ثلاثة متغيرات لها أثرها القوي في تعثر السياحة الحموية بالولاية، وهي المستثمر (66)، منبع (34)، وإدارة السلطة الوصية (19)، في حين أن مؤشرات التركيز على القوانين والتشريعات، والعقار السياحي، لا تعد أحد العوائق التي تسهم في تعثرها، وخلصت الدراسة إلى أن يمكن للشراكة الاستثمارية العامة والخاصة أن تنعش السوق السياحي الكامن في لمجال الحموي بالولاية، شريطة إدراجها ضمن أولويات الاستثمار. Ouargla state is considered the first nationally in the number of heat sources, as it has 39 heat sources, 15 of which have a high flow and therapeutic value out of a total of 282 sources in Algeria. The study aimed to clarify the reality of this tourism and to identify the reasons and problematics of its failure at the state level, based on a descriptive analysis Methodology of statistics obtained from the Ministry concerned with tourism and the State Directorate of Tourism, documents, videos and interviews on the subject with relevant authorities. The study concluded that the problem of medical tourism in its hospital part, the case of febrile water springs, based on the indicators of focus for stakeholders in the same field focused on three variables that have a strong impact on the failure of febrile tourism in the state; It is the investor (66), the upstream (34), and the administration of the guardianship authority (19), while the indicators focus on laws and legislation, and the tourist real estate, is not one of the obstacles that contribute to its failure. Also, the study concluded that the public and private investment partnership can revive the potential tourism market in the febrile field in the state, provided that it is included among the investment priorities.
Keywords: السياحة العلاجية -- المؤسسات الاستشفائية -- التنمية السياحية -- الاقتصاد الجزائري